2020
DOI: 10.1172/jci.insight.139837
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 loss radiosensitizes head and neck squamous cell carcinoma to SMAC mimetic–induced necroptosis

Abstract: Caspase-8 ( CASP8 ) is one of the most frequently mutated genes in head and neck squamous carcinomas (HNSCCs), and CASP8 mutations are associated with poor survival. The distribution of these mutations in HNSCCs suggests that they are likely to be inactivating. Inhibition of CASP8 has been reported to sensitize cancer cells to necroptosis, a regulated cell death mechanism. Here, we show that knockdown of CASP8 renders HNSCCs susceptible to necroptosis by a second m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Does an in‐depth study of the connection between caspase‐8 and precancerous lesions help to inhibit the occurrence of cancer? Interestingly, in head and neck squamous cell carcinoma (HNSCC), the inhibition of caspase‐8 and the second mitochondria‐derived activator of caspases (SMAC) derived from the mitochondria can induce necroptosis to enhance the radiosensitization effect on HNSCC 77 . Fianco et al 61 found that caspase‐8 could maintain tumor transformation in human glioblastoma multiforme (GBM) in vitro.…”
Section: Impact Of Caspase‐8 In Cancer “Panoptosis”mentioning
confidence: 99%
“…Does an in‐depth study of the connection between caspase‐8 and precancerous lesions help to inhibit the occurrence of cancer? Interestingly, in head and neck squamous cell carcinoma (HNSCC), the inhibition of caspase‐8 and the second mitochondria‐derived activator of caspases (SMAC) derived from the mitochondria can induce necroptosis to enhance the radiosensitization effect on HNSCC 77 . Fianco et al 61 found that caspase‐8 could maintain tumor transformation in human glioblastoma multiforme (GBM) in vitro.…”
Section: Impact Of Caspase‐8 In Cancer “Panoptosis”mentioning
confidence: 99%
“…We next examined the genetic alterations of TP53 and CASP8 , which are important molecules that modulate the cell apoptosis pathway 5 , 24 , 25 . The genetic alterations of TP53 and CASP8 from HNSCC TCGA datasets were displayed by Oncoprint, which showed 71% TP53 and 13% CASP8 mutation rates, mainly in HPV(−) HNSCC (Supplemental Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we investigated the genetic alteration rates of TP53 and CASP8 , which are known to play important roles in cell apoptosis in the updated HNSCC TCGA cohort 5 , 24 , 25 . We observed the differential genetic alterations of TP53 and CASP8 between HPV(−) versus HPV(+) HNSCC (Supplemental Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenic HRAS sensitized fibroblasts to TRAIL-induced apoptosis. In addition, CASP8 cleavage and CASP8, which were also found frequently (11.2%) in head and neck squamous cell carcinomas [ 10 ], are associated with poor overall survival in univariate and multivariate analyses [ 28 ].…”
Section: Discussionmentioning
confidence: 99%